2020
DOI: 10.3390/molecules25071670
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Orange Peel in Orange Jam: Evaluation of Sensory, Physicochemical, and Nutritional Characteristics

Abstract: Orange is highly nutritious and a source of phytochemical compounds. However, its by-products are usually discarded. In this study, we evaluated the effect of orange peel (OP) addition in orange jam on sensory, physicochemical, and nutritional characteristics. Four jam formulations were elaborated with different OP levels: OP0 (standard), OP4, OP8, and OP12 (Orange Peel 0, 4, 8 and 12%, respectively). All samples were evaluated for sensory acceptability, and physicochemical and nutritional composition. The add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 56 publications
3
28
0
1
Order By: Relevance
“…The highest TSS values detected for added samples(OP) could be linked to highest amount of pectina of orange peel. As previous studies reported [11], the increase of TSS depends on the formation of hydrogen bridges between sugars and citric and on the degradation of sucrose in glucose and fructose.…”
Section: Discussionsupporting
confidence: 59%
“…The highest TSS values detected for added samples(OP) could be linked to highest amount of pectina of orange peel. As previous studies reported [11], the increase of TSS depends on the formation of hydrogen bridges between sugars and citric and on the degradation of sucrose in glucose and fructose.…”
Section: Discussionsupporting
confidence: 59%
“…According to the panelists, black plum jam had good color, high flavor and spreadability and acceptable with panelists. Teixeira et al [46] reported that the addition of up to 8% orange peel in jam maintains sensory acceptability similar to that of the standard product.…”
Section: Sensory Attributesmentioning
confidence: 97%
“…The firmness, cohesiveness, consistency and index of viscosity of black plum peel marmalade samples ranged 4.96-14.53 N, 9.96-20.44 N, 76.05-213.19 N.s, and 11.05-22.06 N.s, respectively. Teixeira et al [46] studied the addition of orange peel on orange jam. The addition of orange peel reduced the adhesiveness, while improved the gumminess, chewiness, and elasticity.…”
Section: Texture Measurementmentioning
confidence: 99%
“…Citrus plants are among the most important dietary sources of flavonoids, which influence their flavor and medicinal value 11 , 12 . Flavonoids exhibit tissue and species specificity in citrus plants 13 .…”
Section: Introductionmentioning
confidence: 99%